Low velocity impact response of carbon fiber laminates fabricated by pulsed infusion: A review of damage investigation and semi-empirical models validation. (February 2016) - Antonucci, V.; Caputo, F.; Ferraro, P.; Langella, A.; Lopresto, V.; Pagliarulo, V.; Ricciardi, M.R.; Riccio, A.; Toscano, C.
Abstract: The research reported in this paper was aimed mainly to investigate the different NDE techniques on specimens made by a new process labeled as "pulsed infusion", very crucial for voids content under critical loading conditions. The impact load, in fact, is critical for composite laminates due to their anisotropy, in particular in extreme temperature conditions due to their brittleness. An additional and very relevant aim was to collect a large number of experimental results to supply useful information for the numerical models needed to simulate the dynamic behavior of composite laminates. At the aim to investigate the response under dynamic loads of laminates fabricated by a new vacuum assisted technology labeled as "pulsed infusion", rectangular carbon fiber composite specimens were subjected to low velocity impact tests. Experimental tests up to complete penetration and at different energy levels, were carried out by a modular falling weight tower. All the parameters related to the phenomenon, like penetration energy, maximum force and indentation depths, were used to validate existing semi-empirical and numerical models. The largely used ultra sound technique (US) was adopted to investigate the delamination together with the thermo graphic technique. The results of the measurements were compared with data obtained on the same specimens by holographic analysis (ESPI). One of the scope was to investigate the crucial internal impact damage and assess the ability of an unconventional ND system (ESPI) in giving right information about non-visual damage generated inside composite laminates subjected to dynamic loads. Moreover, some of the specimens were cut to allow the fractographic analysis. The efficiency of the above mentioned new fabrication technology was studied also comparing the results with measurements from literature on impacted autoclave cured laminates. By the comparison between the results, good agreements were found denoting the efficiency and the applicability of the new fabrication and the used NDE methods.